STUDENTS’ PERCEPTION ON USING QUIZLET IN LEARNING ENGLISH - Abubakar, Multazam (elstic : english language linguistics culture, 2024)
This study examines students' perception on using Quizlet in learning English class eight at MTsN 1 Kota Makassar. This study aims to determine whether the students have positive or negative perception. The method is quantitative. Data were collected by giving questionnaires through the Google form. The subjects of this study were 40 students of grade eight Tahfidzh 1 at MTsN 1 Kota Makassar. To determine the sample, the researcher used purposive sampling technique. The results of this study indicated positive perceptions of the 22 statements. Based on the four adopted indicators such as ease of access having the highest percentage of 86.25%, then perceived usefulness with the highest percentage of 81.87%, communication and interaction with the highest percentage of 83.75%, then on student satisfaction has the highest percentage of 80.62%. Researcher found that respondents had positive perceptions about using Quizlet. Students stated that Quizlet is a learning while playing application because the features provided make students are not feel bored, and students enjoy to using that system. Students also admit that besides being fun, Quizlet can also increase their vocabulary. The implication of this research is that Quizlet can be used as a learning media as well as an assessment media to support teaching and learning processes. Therefore, the teacher at the school has implemented Quizlet in the English vocabulary subject. However, before accessing Quizlet should the students consider the stability of the internet connection before implementing the application in class.